Nevladne organizacije na področju kulture - Rakar, Tatjana (Teorija in praksa, 2025)
In the article we focus on the position of NGOs in the field of culture in a comparative context with other NGOs in Slovenia, and analyse their cooperation with government authorities and political actors. The results show the considerable local embeddedness of NGOs, yet also a relatively low level and informal form of participation, in contrast to the idea of participatory governance. The cultural NGOs–state relationship can be characterised as a model of ‘separate autonomy’, with a medium level of public funding, a medium level of NGO autonomy, and a low level of civil dialogue.
Keywords: civil dialogue; civilni dialog; culture; Društva, združenja ipd.; kultura; Nepridobitne organizacije; nevladne organizacije; NGOs; participacija; participation